A novel approach to synthesize the amorphous carbon-coated WO3 with defects and excellent photocatalytic properties. (15th September 2016) - Chen, Pengqi; Qin, Mingli; Chen, Zheng; Jia, Baorui; Zhao, Shangjie; Wan, Qi; Qu, Xuanhui
Abstract: Amorphous carbon-coated tungsten oxide nanocrystals were synthesized via the ultra-rapid solution combustion synthesis method with low-cost, non-toxic starting materials. The amount of glucose played an important role in the synthesis of WO3-x with a suitable amount of carbon. Carbon-coated tungsten oxide existed in the form of round particles with size of 150 nm and the WO3-x nanorods with the length of 20 nm and diameter of 5 nm. After oxidization by H2 O2, the WO3-x particles were changed into WO3 with a large amount and variety of defects and kept the original size and nanorod structure. This characteristic resulted in an excellent visible driven photocatalytic performance, and it took about 40 min to degrade the methylene blue (100 mL; 80 mg L −1, MB). Moreover, the material demonstrated good photocatalytic stability under visible light after 5 recycling degradation of MB. The interesting reaction mechanism and the photocatalytic mechanism were studied in this paper. Our study is helpful to design the new photocatalysts, which will have a great application potential in the fields of environmental purification and clean energy. Graphical abstract: The as-synthesized carbon coated WO3 via ultra-rapidly solution combustion synthesis method showed a considerable rate for organic degradation under UV–visible light and good stability. This excellent performance is attributed to the synergistic effect of the amorphous carbon and the large amounts of defects. Highlights: Our combustion method is time & energy efficient, convenient and low-cost. The suitable content of carbon promoted the photocatalysis ability effectively. The defects of powder we designed promoted the photocatalysis ability effectively. The synthesized powder showed a good stability of organic degradation.